Intracranial angiomatoid fibrous histiocytoma: report of a rare case - Tabibkhooei, Alireza; Asgarzadeh, Leila; Sadeghipour, Alireza; Vafaee Shahi, Mohammad (Iranian Journal of Child Neurology, 2022)
One rare and low-grade soft tissue tumor with intermediate malignant potential is angiomatoid fibrous histiocytoma (AFH) و which occurs mainly in children and adolescents. The tumor naturally tends to local recurrence and recurrent hemorrhage but rarely to remote metastasis. AFH has been reported in different organs; however, there are rare reports of primary intracranial AFH. The diagnosis of AFH may be difficult due to its occurrence at multiple unusual anatomic sites and its spectrum of morphologic patterns; thus, it is especially importantto diagnose it correctly because of the small risk of metastasis and death. The lesion is simply confused with a hematoma, soft tissue hemangioma, or malignant fibrous histiocytoma from clinical and radiographical aspects. We report a case of intracranial AFH in a 5-year-old boy. The tumor is a heterogeneous intra-axial with a size of 78*73mm at the right front temporal. There was also an extra-axial mass measured 8*12mm at the left superior frontal lobe in favor of metastasis. The diagnosis was confirmed using radiographical, immunohistochemical, and molecular tests. AFH is a rare tumor with a high probability of misdiagnosis. Surgeons must be aware of the presence of AFH and conduct a careful followup